Adaptation of Digital Marketing of Coffee MSME Products to Digital Transformation in the Era of the Covid-19 Pandemic - Sri Watini; Haznah Latifah; Dudi Rudianto; Nesti Anggraini Santoso (Pandawan Sejahtera Indonesia, 2022)
The spread of the Covid-19 virus impacts all aspects, one of which is the economic aspect. To maintain coffee MSME products during the pandemic, MSME Coffee players have adapted to government policies, namely by utilizing digital technology to synergize with today's digital transformation. Observing and studying literature is used as a research method, collecting information so that the adaptation process can run smoothly as expected. After the MSMEs of Coffee Products have adapted the digital business in the digital marketing section, the results obtained are the presence of Instagram Social Media, Blogs, Online Stores, and new Payment Methods. The use of this technology certainly impacts both MSME actors and consumers who find it easy. The hope is that the research will be able to develop an online marketplace and also assess the level of consumer satisfaction with the use of digital media on this MSME Coffee product.